Plant density effects on growth and yield of tropical soybean - Amissah-Arthur, A.A.; Jagtap, S.S.; Dashiell, Kenton E. (1999)
Two field experiments were conducted in a subhumid environment with tropically developed soyabeans to plant densities of 13.3-57.1 plants/m2. Grain yield, total dry matter GDM) and seeds/m2 were highest at 57.1 plants/mz. There was a linear relationship betweenT DM, seeds/m2a nd crop growth rate during flowering to seed-fiU( RI to R5) and a quadratic response of seeds/m2 to TDM (RS). Increasing plant densities gave increased grain yields.